The analysis of influence of uncertainty factors on mathematical modeling of process of reverse expansion of ammonia in low-speed reciprocating compressor stage. Part 1 - D. Kh. Sadvakasov; G. I. Chernov; V. L. Yusha (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper presents an analysis of the influence on the mathematical modeling of the process of reverse expansion of ammonia in the area of wet steam, implemented in the working chamber of the reciprocating compressor stage, of such uncertainty factors as the method for calculating the heat transfer coefficient, the surface temperature of the wall of the working chamber and the degree of dryness at the beginning of the process of reverse expansion. The mathematical model is based on the equations of the first law of thermodynamics for a body of variable mass, the equation of state of a real gas, the Clausius– Clausius and Newton–Richmann equations. The results of the calculation showed that the instantaneous values of the pressure and temperature of ammonia, as well as its degree of dryness during reverse expansion in the wet steam region, significantly depend on the chosen method for calculating the heat transfer coefficient. The process under consideration is also significantly influenced by the temperature of the walls of the compressor working chamber, in which the compression process is implemented, and the degree of dryness of ammonia at the beginning of the expansion process.